DAMPAK COVID-19 TERHADAP PENDAPATAN DAERAH PEMERINTAH KOTA BATAM TAHUN 2020 - Rahmayandi Mulda; Nurhayati Nurhayati; Meri Enita Puspita Sari; Ronal Parlindungan; Muhammad Solihin (Jurnal Administrasi Negara, 2023)
This research is motivated by the ongoing COVID-19 pandemic, which has resulted in a decline in both national and regional economic growth rates. It is suspected that this has had repercussions on the revenue of the City Government of Batam. The primary objectives of this study are to analyze the impact of COVID-19 on the city's revenue and to assess the policies implemented by the City Government of Batam to enhance revenue during the COVID-19 pandemic. The research employs a qualitative methodology, involving data collection through interviews, observations, and document analysis. The findings indicate a significant reduction in Batam City's Local Own Source Revenue (PAD) due to the adverse effects of COVID-19, particularly within the tourism sector, which serves as a primary source of regional income. In contrast, the intergovernmental transfer sector remained unaffected and even experienced an increase in revenue. Additionally, other revenue sources witnessed growth due to the stability of the trade and industry sectors during the pandemic. Overall, the impact of COVID-19 on Batam City's revenue in 2020 was not excessively detrimental, as the Regional Budget (APBD) continued to increase from 2019. The City Government of Batam implemented various policy measures, such as aligning development programs with the central government, promoting the region's potential to both the central government and investors, and enhancing the quality of public services. These actions facilitated the allocation of additional funds from the central government. Research recommendations encompass a focus on the development of innovative development programs, the recovery of the tourism sector, the diversification of income sources, and the enhancement of inter-governmental collaboration.